Resilience among organ donation coordinators: a Canadian mixed-methods study - Silva, Amina R.; Rochon, Andrea; Hornby, Laura; Lotherington, Ken; James, Lee; Webster, Richard; Sucha, Ewa; Sarti, Aimee; Dhanani, Sonny; Silva e Silva, Vanessa (Frontiers in Public Health, 2024)
Disclosure K.L. and L.J. are Canadian Blood Services employees. L.H. was a paid research consultant for Canadian Blood Service. S.D. receives a stipend from Ontario Health Trillium Gift of Life as a Hospital Donation Physician. The other authors have no conflicts of interest to declare. Funding This work was financially supported by CHAMO (Children Hospital Academic Medicine Organization) research innovation grant from Children's Hospital of Eastern Ontario and Canadian Blood Services. Canadian Blood Services receives funding from the provincial and territorial Ministries of Health and the federal government, through Health Canada. The views expressed herein do not necessarily represent the views of the federal, provincial, or territorial governments. Canadian Blood Services is a national, not-for-profit charitable organization that manages the supply of blood and blood products in all provinces and territories in Canada (with the exception of Quebec) and oversees the Canadian Blood Services Stem Cell Registry. In 2008, Canadian Blood Services became responsible for national activities related to organ and tissue donation and transplantation (OTDT), which includes national system development and operation of interprovincial organ sharing programs. Canadian Blood Services is not responsible for the management or funding of any Canadian organ donation organization or transplant program.